EXPLOSIONS IN ICE - LIVINGSTON, CLIFTON W. (1960)
Twenty-four instrumented and 106 uninstrumented blasts ranging in weight from 2.5 to 40 lb of four types of explosives were detonated above, in contact with, and at various depths below the ice surface. The tests were conducted at the edge of the Greenland Ice Cap, near Camp Tuto, during the summer of 1957. Under-ice direct shock pressure, air-induced under-ice shock pressure, and airblast pressure from shallow under-ice bursts, contact bursts, and near-contact bursts were measured. The apparent crater and the true crater were measured, and the mechanics of the fracture process were studied. The height to which the flyrock was thrown was measured using motion pictures, and ground rise and venting phenomena were studied. Sixty-six seismic records were taken.